Human Dimensions of Chronic Wasting Disease in Wisconsin - Edwards, Samantha; Kleintjes Neff, Paula K. (My University, 2019)
CWD is a disease caused by prions (an infectious protein particle similar to a virus). CWD can affect deer, elk, moose and reindeer. The first case of CWD in Wisconsin was discovered in 2002 and in Eau Claire County in 2018. Its arrival initiated the creation of the Chippewa Valley CWD Advisory Team (CVCAT). The CVCAT is made up of 7 members of the public that have prior knowledge of deer herd management and hunting practices. The goal of CVCAT is to provide the WDNR recommendations regarding local surveillance areas and methods, and management options for white-tailed deer potentially exposed to CWD. The objective of this study is to qualitatively assess the effectiveness of the CVCAT, i.e., assessing what the public thinks it wants and what the WDNR would like to see happen. The assessment includes interviewing and surveying four focal groups who have a stake in either deer hunting, and/or deer population management (CVCAT members; members of public who attend CVCAT meetings; WDNR employees working directly with CWD; and students/deer hunters in the UWEC Rod and Gun Club). Survey results will be summarized and analyzed to gauge local perceptions of CWD and the effectiveness of the CVAT. The data will then be potentially used by the WDNR as they face the challenge of working with the public to manage deer and this emerging infectious disease.
Color poster with text, charts, photographs, and maps.
Keywords: Chronic Wasting Disease – Wisconsin; Wisconsin Department of Natural Resources; Survey results; Posters